EXTRAS (Fiep Bulletin - online, 2012)
PRINCE FAISAL BIN FAHAD INTERNATIONAL PRIZE FOR ARAB SPORT DEVELOPMENT RESEARCHESFIEP DELEGATESSTRUCTURE OF THE FIEPFIEP EXECUTIVE BOARD 2008-2012ABOUT THE FIEPFIEP CROSS OF HONORSUBSCRIPTION FORM